2019
DOI: 10.31665/jfb.2019.5186
|View full text |Cite
|
Sign up to set email alerts
|

Guarana as a source of bioactive compounds

Abstract: A high daily intake of fruits and vegetables is an important strategy to promote health. The mechanism explaining the health benefits of plant food materials is attributed, at least in part, to their high content of bioactive phenolics. Guarana (Paullinia cupana) is a typical product from Amazon biota and, mainly as a source of caffeine; its seeds are commonly used as stimulants. However, guarana seeds are also rich in catechin, epicatechin, procyanidin B1, and procyanidin B2. Guarana exhibits potential health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Polyphenols bind proteins due to the formation of hydrogen bonds or addition of nucleophiles to oxidized phenolics as quinones and specific methods have been developed for discovering new enzyme inhibitors aiming at designing new functional foods and/or nutraceuticals [ 65 ]. Accordingly, several sources of phenolic compounds have been tested for their inhibitory activity toward alpha-glucosidase [ 66 , 67 ]. The antidiabetic effect of natural compounds has been in the spotlight of various researchers [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols bind proteins due to the formation of hydrogen bonds or addition of nucleophiles to oxidized phenolics as quinones and specific methods have been developed for discovering new enzyme inhibitors aiming at designing new functional foods and/or nutraceuticals [ 65 ]. Accordingly, several sources of phenolic compounds have been tested for their inhibitory activity toward alpha-glucosidase [ 66 , 67 ]. The antidiabetic effect of natural compounds has been in the spotlight of various researchers [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brazil is the only commercial producer of guarana, with a yield of 3,726 metric tons yr −1 in 2018 (IBGE, 2019). Several studies have demonstrated guarana as a source of bioactive compounds, methylxanthines and catechins, with energetic and antioxidant properties (Marques, Ferreira, Paula, Klein, & Mello, 2019; Moustakas et al., 2015; Ruchel et al., 2017; Salomão‐Oliveira, Lima, Marinho, & Carvalho, 2018; Silva, Soares‐Freitas, Sampaio, Camargo, & Torres, 2019; Yonekura et al., 2016).…”
Section: Introductionmentioning
confidence: 99%